Analisis Hubungan Antara Aktivitas Fisik Dan Kontrol Gula Darah Pada Pasien Diabetes - Imelda Appulembang; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Diabetes mellitus is a chronic disease characterized by elevated blood sugar levels due to impaired insulin secretion or function. One of the main pillars of diabetes management, in addition to drug therapy and dietary adjustments, is regular physical activity. Physical activity is known to improve insulin sensitivity and help control blood sugar levels. This study aims to analyze the relationship between physical activity and blood sugar control in diabetes patients. This study used quantitative methods with an analytical design and a cross-sectional approach. The study sample was diabetes mellitus patients undergoing routine check-ups at health care facility X. Data were collected through a physical activity questionnaire and blood sugar level checks, then analyzed using the Chi-Square test. The results showed a significant relationship between physical activity levels and blood sugar control (p < 0.05). The conclusion of this study is that adequate and regular physical activity plays an important role in maintaining blood sugar control in diabetes patients.